Essentials of electromagnetics for engineering - De Wolf, David A. (Cambridge : Cambridge University Press, 2001)
Provides a clearly-written introduction to the key physical and engineering principles of electromagnetics. Throughout the book, the author describes the intermediate steps in mathematical derivations that many other textbooks leave out. The author begins by examining Coulomb's law and simple electrostatics, covering in depth the concepts of fields and potentials. He then progresses to magnetostatics and Maxwell's equations. This approach leads naturally to a discussion of electrodynamics and the treatment of wave propagation, waveguides, transmission lines, and antennas. At each stage, the author stresses the physical principles underlying the mathematical results. Many homework exercises are provided, including several in Matlab and Mathematica formats. The book contains a separate chapter on numerical methods in electromagnetics, and a broad range of worked examples to illustrate important concepts. It is suitable as a textbook for undergraduate students of engineering and applied physics taking introductory courses in electromagnetics.
Includes bibliographical references (p. [498]-499) and index.
Buku Bacaan Asas Fakulti (TM)
Keywords: Electromagnetism; Electronics; Electrical engineering